2016
DOI: 10.1007/s10815-016-0818-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pregnancy rate following frozen embryo transfer is higher with blastocysts vitrified on day 5 than on day 6

Abstract: The clinical pregnancy rate following frozen embryo transfer is significantly lower with blastocysts vitrified on day 6 compared to blastocysts vitrified on day 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
39
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 23 publications
14
39
0
2
Order By: Relevance
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, 23 studies were included in the following meta-analyses. 4,6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The main characteristics and assessment for risk of bias of the included studies are presented in Table 1.…”
Section: Results Of the Searchesmentioning
confidence: 99%
“…However, when all the blastocysts were taken in to account, the CRP and IR of the D5 blastocysts were higher than those of the D6 blastocysts [18]. Hass et al demonstrated that even the CPR of morphologically good quality D6 blastocysts is significantly lower than that of D5 blastocysts in FET cycles [16]. Additionally, Ferreux et al reported that no matter what the blastocyst quality was, the LBR of D6 blastocysts following FET was significantly lower than that of D5 blastocysts [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports showed equivalent outcomes between blastocysts formed and cryopreserved on day 5 (D5 blastocysts) and blastocysts formed and cryopreserved on day 6 (D6 blastocysts) [11][12][13][14]. Meanwhile, there is a growing body of evidence indicating that the CPR, IR, and live birth rate (LBR) with D5 blastocysts are higher than with D6 blastocysts in FET cycles [15][16][17][18][19][20]. Therefore, whether the day of blastocyst formation affects clinical outcomes remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies also have conflicting results. Some studies suggest that day 6 blastocysts have comparable clinical outcomes with day 5 blastocysts (5,(13)(14)(15)(16)(17)(18), while other studies suggest that clinical outcomes are better with day 5 blastocysts (19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%